Hydrogen Adsorption/desorption on lithium Alanat Catalyzed by Ni/C for Sustainable Hydrogen Storage - Icha Amelia; Dedi Rohendi; Addy Rachmat (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
LiAlH4 alloy has been believed to have the potential to become one of the hydrogen storages with high storage capacity. In this research, the formation of LiAlH4 alloys with dope and undope Ni/C catalysts and characterization and testing of hydrogen adsorption/desorption capacities using these alloys have been carried out. The alloy was made by the milling method and the resulting alloy was characterized using XRD analysis. The adsorption capacity test of the alloy was carried out by the gravimetric method at various pressures. The adsorption capacity of the LiAlH4 alloy by adding additives in the form of Ni/C as much as 5%w/w was proven to increase the hydrogen adsorption capacity compared to undope a catalyst with the highest storage capacity at a pressure of 3 bar of 13.06%w/w compared to undope a catalyst of 9.84%w/w at the same pressure. Meanwhile, the highest hydrogen desorption capacity was 53.56% w/w (dope catalyst) and 41.75% w/w (undope catalyst).